Realization of Ultra-compact All-optical Universal NOR Gate on Photonic Crystal Platform - F. Parandin (Journal of Electrical and Computer Engineering Innovations, 2021)
Background and Objectives: Universal NOR gate is one of the most important gates in digital design. The all-optical NOR gate can be designed using photonic crystals. These types of gates have a small size and can be integrated.Methods: In this paper, an optical NOR gate is designed based on 2D photonic crystals. A square lattice has been used to design this structure. This logic gate has two main inputs, a bias input and an output. Because the output of the NOR gate must be “1” for zero inputs, a bias input is required. A combination of linear and point defects has also been used to create waveguides. Results: One of the characteristics of this structure is its small size for use in optical integrated circuits. The use of a small number and simple point defects makes the design of this gate easier. The obtained delay time for this gate is 0.06ps. Due to these features, this gate can be used in high-speed optical integrated circuits.Conclusion: In this paper, an all-optical NOR logic gate is designed and simulated using photonic crystals. The use of a small number of point defects has reduced the delay time of this gate. The proposed NOR gate can be used in high-speed optical integrated circuits.